Résistances de femmes face aux risques de subsistance à l’île Maurice. Travail, éthique et subjectivité politique de Shakti - Colette Le Petitcorps (Genre, Sexualité et Société)
This article is about the resistance of women who face the super exploitation of their labour in the context of the threat to their household survival by capitalist accumulation. I trace back the recent historical evolution of women’s daily life and their role in the labourers’ households of Mauritius old plantation society. The analysis focuses on the experience of a woman who tells the story of her fight for survival, from her childhood in the plantations system to her current position in domestic service. Her narrative gives an account of the constitution of a subject empowered with a political ability to challenge the legitimacy of the actors and institutions that put their household survival at risk. The discursive analysis of her subjectivity at work and dissent to power relations unveils the existence of some collective practices among vulnerable women who aim at deciding autonomously on the way to organise their social reproduction.